The ‘In-Betweenness’ of Emerging Newcomer Scholars - Kusari, Kaltrina (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2020)
In 2015, the European Union experienced a 51% increase in asylum requests. Kosovars constituted the fourth largest group of these asylum seekers, yet only 2.3% were granted asylum. Rejected applicants continue to be forcefully returned to Kosovo partly because repatriation, or the right to return to one’s country of origin, is the EU’s preferred solution to migration crisis. A significant body of research substantiates that repatriation is neither voluntary nor a durable solution. To address the discrepancy between existing evidence and the adoption of repatriation as a sustainable solution, I employed Critical Discourse Analysis to explore the involuntary repatriation of rejected asylum seekers from Kosovo. Findings from semi-structured interviews with rejected-asylum-seekers suggest that this population uses discourses which construct EU countries as superior to Kosova and migration to these countries as an opportunity for a better life. These discourses uphold the Global North superiority and encourage participants to consider remigration, rather than reintegration, as a solution to their current challenges. These findings have implications for repatriation policies and highlight important aspects of being an emerging newcomer scholar. My focus on Kosovo was partly a result of the fact that I am originally from Kosovo yet have completed my post-secondary and graduate education in Canada. As such, this research brief explores how the identity of emerging newcomer scholars is shaped by transnational research.